The Effectiveness of the Blended Learning Approach Based on Edmodo to Enhance Student Learning Outcomes in English Courses - Rully Khoeru Solihin; Lanlan Muhria (Scope : Journal of English Language Teaching, 2023)
A learning model called blended learning mixes online and face-to-face instruction. It includes multiple implementation techniques, instructional models, and learning styles. The Edmodo application media is one of the educational chances supplied by exploiting current ICT advances. The purpose of this study was to determine the effectiveness of learning using the Edmodo-based blended learning model in improving student learning outcomes in English courses. This study employed an experimental research methodology. Data are grouped and extraneous information is reduced due to the descriptive qualitative approach's framework, which collects data through testing, observation, and documentation. In this study, data analysis started with data collecting and was then condensed, including summarizing, choosing the most crucial information, concentrating on it, searching for themes and patterns, and removing irrelevant information. Based on the research findings, two approaches—online via the Edmodo application and offline—are recommended for implementing the blended learning strategy based on Edmodo (face to face). Students use Edmodo to interact with lecturers and other students during online lectures. Beforehand, the lecturer created a virtual class on Edmodo and connected all the students to it. The in-person meetings include group discussions based on the material covered in the online classes. Events held in person can also be hosted using the Edmodo app. Based on test results and an analysis of the learning outcomes of students who used the blended learning strategy built on Edmodo, it is rated in the very good category.